Comparison of chest-CT findings of Influenza virus-associated pneumonia in immunocompetent vs. immunocompromised patients. Issue 6 (June 2015) - Kloth, C.; Forler, S.; Gatidis, S.; Beck, R.; Spira, D.; Nikolaou, K.; Horger, M.
Highlights: Patterns of pulmonary infiltration caused by Influenza viruses do not significantly differ between immunocompetent and immunocompromised patients or between different types and subtypes of Influenza virus. Patterns of pulmonary infiltration caused by Influenza viruses seem to be interchangeable which might in part explain the great overlap in CT-imaging findings that has been reported in the past. Interestingly, pattern transition from interstitial into airway-centric pattern seems to be frequent in immunocompromised patients receiving specific antiviral therapy, whereas the conversion of the airway-centric pattern into an interstitial pattern was observed more frequent in immunocompetent patients developing ARDS. Abstract: Purpose: To retrospectively compare CT-patterns of pulmonary infiltration caused by different Influenza virus types and subtypes in immunocompetent and immunocompromised patients for possible discrimination. Materials and methods: Retrospective database search at our institution yielded 237 patients who were tested positive for Influenza virus type A or type B by bronchoalveolar lavage between January 2009 and April 2014. Fifty-six of these patients (female 26; male 30; median age 55.8 y, range 17–86 y; SD ± 14.4 y) underwent chest-HRCT due to a more severe clinical course of pulmonary infection. We registered all CT-findings compatible with pulmonary infection classifying them as airway predominant (tree-in-bud, centrilobular nodules, bronchial wall thickening ± peribronchial ground-glass opacity and consolidation) vs. interstitial-parenchymal predominant (bilateral, symmetrical GGO, consolidation, crazy paving and/or interlobular septal thickening). Twenty-six patients (46.4%) had follow-up CT-studies (0.78 mean, SD ± 5.8 scans). Results: Thirty-six patients were immunocompromised (group I) whereas 20 patients were immunocompetent (group II). An airway-centric pattern of infection was found in 15 patients (group I) and 14 patients (group II) whereas an interstitial-parenchymal predominant pattern was found in 14 patients (group I) and 2 patients (group II). Eleven patients had a mixed pattern with no clear assignment to one group. At FU, 12 patients from group I and 3 from group II showed transitional infiltration patterns: in 10 patients from interstitial-parenchymal into airway predominant pattern and in five patients from airway predominant into interstitial-parenchymal. No significant differences in the pattern of pulmonary infection were found between different types and subtypes of Influenza viruses. Conclusion: Patterns of pulmonary infiltration caused by Influenza viruses do not significantly differ between immunocompetent and immunocompromised patients or between different types and subtypes of Influenza virus. One possible explanation for this could be the temporarily interchangeable character of pulmonary infiltration in this infection.